The Influence of Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), Return on Assets (ROA), and Loan To Deposit Ratio (LDR) on Financial Sustainability in Regionally Owned Enterprises (BUMD) Bank Pasar Kulon Progo for the 2018-2023 Period - Kristin Wijayanti, Eva Farida; Prasetya, Bangun Putra (Journal Of Management Analytical and Solution (JoMAS), 2024)
Bank Pasar Kulon Progo plays a key role in promoting regional economic growth and improving welfare. To maintain financial stability, it is essential to assess factors influencing financial sustainability. This study examines the impact of Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), Return on Assets (ROA), and Loan to Deposit Ratio (LDR) on the Financial Sustainability Ratio (FSR) of Bank Pasar Kulon Progo from 2018 to 2023. A quantitative approach was used, analyzing financial report data with purposive sampling. Multiple linear regression was applied to assess the relationships between the variables. The results show that CAR, NPL, ROA, and LDR have a significant impact on FSR, collectively explaining 79.5% of its variation (RÂ² = 0.795). The remaining 20.5% is influenced by other factors outside the model. These findings suggest that effective management of CAR, NPL, ROA, and LDR is crucial for ensuring the financial sustainability of Bank Pasar Kulon Progo.